Study on the Influence Rule of High-Pressure Water Jet Nozzle Parameters on the Effect of Hydraulic Slotting. (22nd August 2022) - Gu, Beifang; Hu, Ruili; Wang, Longkang; Xu, Guanchao
Abstract : In order to get the appropriate nozzle parameters, numerical simulation and field tests are used to investigate the influence of high-pressure water jet nozzle parameters on the effect of hydraulic slotting. A nozzle model is created by using FLUENT software. For different nozzle contraction angles, outlet diameters, and straight column section lengths, the distribution rules of the velocity of the water jet and dynamic pressure on the central and vertical axes are obtained, and the parameters for the best nozzle effect are determined. The relationship between the nozzle contraction angle gradient, the inlet water pressure, and the nozzle outlet water velocity is discovered. A mathematical model of the nozzle outlet water velocity of the water jet is established. The depth, width, and volume of the hole generated by the nozzle impact are employed as indications for inquiry, and field measurements are used to derive the results of nozzle geometry parameter optimization. The field tests validate the numerical simulation conclusions, and the results have theoretical and practical guidance for hydraulic slotting in coal mines and get the appropriate nozzle parameters specially.